2005
DOI: 10.1007/bf02760578
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of kangaroo mother care in Mumbai

Abstract: KMC is a simple and feasible intervention; acceptable to most mothers admitted in hospitals. There may be benefits in terms of reducing the incidence of hypothermia with no adverse effects of KMC demonstrated in the study. The present study has important implications in the care of LBW infants in the developing countries, where expensive facilities for conventional care may not be available at all place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
72
3
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 9 publications
11
72
3
3
Order By: Relevance
“…Mohammadzadeh et al and Basiri et al showed that there was no significant differences between the two groups in nosocomial infection (P > 0.05) (25,27). These findings were similar to the Kadam et al report that observed no significant differences in the incidence of sepsis (51). on the other hand, Charpak reported that infection was milder in children receiving the KMC (8).…”
Section: Infectionsupporting
confidence: 90%
“…Mohammadzadeh et al and Basiri et al showed that there was no significant differences between the two groups in nosocomial infection (P > 0.05) (25,27). These findings were similar to the Kadam et al report that observed no significant differences in the incidence of sepsis (51). on the other hand, Charpak reported that infection was milder in children receiving the KMC (8).…”
Section: Infectionsupporting
confidence: 90%
“…[2][3][4][5]29,30 As found in our study, mothers in hospitals have associated KMC with a sense of empowerment, fulfillment, and confidence in caring for their newborns. 30,31,38 In addition, mothers have found that KMC reduces their stress level and increases their attachment/bond to Community-based KMC in India GL Darmstadt et al their newborn.…”
Section: Acceptance Of Community-based Stscsupporting
confidence: 70%
“…The technique has found widespread acceptance for care of medically stable, hospitalized LBW infants weighing <2000 g. [2][3][4][5][6][7][8] The practice of KMC in hospitalized LBW infants has been associated with a number of benefits, and is now considered to be at least as good as standard care with incubators. 2 Potential benefits include improved maternal-infant bonding, more rapid transition to physiological stability following birth, reduced crying and longer periods of alertness, improved breastfeeding and growth, reduced incidence of hypothermia and serious bacterial infections, and earlier discharge from hospital.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, there was no difference in mean hospital stay between the two groups, in contrast with the lower stays in a kangaroo group observed by Charpak et al 18 and Cattaneo et al 25 These data are in agreement with work published by et al 26 and Roberts et al 24 In contrast, Ramanathan et al 13 and Charpak et al 18 did find that kangaroo method babies had shorter stays.…”
Section: Discussionsupporting
confidence: 91%
“…There was no difference in relation to certain intercurrent clinical conditions, in contrast with Sloan et al, 26 who observed lower frequencies of apnea and infections in a kangaroo group, with Cattaneo et al, 25 who described reduced risk of hypothermia, and with Kadam et al, 26 who found lower incidence of hypothermia, better oxygen saturation and lower respiratory rate in a kangaroo group. Nevertheless, this last study did not find any differences in hyperthermia, sepsis or apnea.…”
Section: Discussionmentioning
confidence: 76%